2009
DOI: 10.2174/157016209789346255
|View full text |Cite
|
Sign up to set email alerts
|

SHIV Infection Protects Against Heterologous Pathogenic SHIV Challenge in Macaques: A Gold-Standard for HIV-1 Vaccine Development?

Abstract: A current debate in the HIV-1 vaccine field concerns the ability of an immunodeficiency virus to elicit a protective response. One argument is that HIV-1 superinfections are frequent in healthy individuals, because virus evades conventional immune surveillance, a serious obstacle to vaccine design. The opposing argument is that protection from superinfection is significant, reflecting a robust immune response that might be harnessed by vaccination to prevent disease. In an experiment designed to address the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The observation that neutralizing antibodies are capable of preventing infection in animal models [52] initially suggested that this kind of response might be able to prevent SI in humans. In support of this hypothesis is a study in which the lack of neutralizing antibody response had been associated with a predisposition to SI [53].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that neutralizing antibodies are capable of preventing infection in animal models [52] initially suggested that this kind of response might be able to prevent SI in humans. In support of this hypothesis is a study in which the lack of neutralizing antibody response had been associated with a predisposition to SI [53].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous laboratories have now demonstrated that infection with one immunodeficiency virus (SIV or SHIV) can protect against subsequent infection with another [4750]. How can this be explained?…”
Section: Hiv-1 Vaccine Development: Non Recombinant Vaccine Stratementioning
confidence: 99%
“…Another noteworthy success was with attenuated SIV nef-deletion mutants (16) and with passive transfers of protective antibodies from SIV infected to naive animals (52). Similarly, SHIV infections have been shown to confer protection against heterologous challenges in animal models (17,46), and healthy HIV-1-infected humans have exhibited significant protective immunity against superinfections (12,43). Perhaps individuals once infected with immunodeficiency viruses are protected against heterologous challenges due to the natural evolution of viruses and respective immune responses within the patients (40,42,56).…”
Section: Tackling Diverse Pathogens With Human Vaccinesmentioning
confidence: 99%